MOST FREQUENTLY DETERMINED CARRIAGES OF INFECTIOUS AGENTS DURING HEALTH - HYGIENE EXAMINATION OF PERSONS EMPLOYED IN FOOD PRODUCTION AND TRADE - Silovska Nikolova Aleksandra; Trajchev Metodija; Pejkovski Zlatko (University Ss. Cyril and Methodius in Skopje, 2024)
Food safety is one of the key factors for consumer health. Therefore, a lot of attention has been paid in the last few decades to the identification of biological hazards in food. They represent a very serious danger to the health and safety of consumers.The health status of food handlers is a very significant factor for food safety. For those reasons, it is necessary that they regularly perform the prescribed health-hygiene examinations in order to prevent the secondary contamination of food, thereby preventing the development of food-borne diseases. During the research period 2011-2020, it was established that 11,347 people did not have a health-hygiene examination during the inspections carried out by the Food and Veterinary Agency in the Republic of North Macedonia.The largest number of persons who did not perform a health-hygiene examination was observed in 2012, i.e. 2276 persons, compared to 2016, when the lowest number of persons (596) who did not perform a health-hygiene examination was ascertained. For the analyzed period, the competent authority removed from work a total of 3170 food handlers due to carriages of infectious agents. In 2012, the largest number of removed persons was recorded (808), compared to 2018 when only 80 persons were removed due to carriage. Regular health-hygiene examinations for employees who are in contact with food allows timely detection of asymptomatic carriers of bacteria and parasites, which will reduce and prevent the development of food-borne diseases
Keywords: food operators, handling food, food handlers, safety, Staphylococcus aureus